LEWY BODY DEMENTIA: A DIAGNOSTIC APPROACH - Nogueira, Carlos Eduardo Rodrigues; de Macedo, Ryan Rafael Barros; Vieira, Carolina Sena; Oliveira, Juliana Cristina Santana Lima Queiroz; Baltazar Júnior, Orlando; de Azevedo, Gabriel Felicio; da Silva, Edvania da Paz; Costa, Fernando Gomes; Silva, Maria Fernanda Filgueira; dos Santos, José Ricardo; Silva, Maria Isabele dos Santos; Seabra, Lucas dos Anjos (Seven Editora, 2026)
Lewy body dementia (LBD) is one of the main causes of neurodegenerative dementia in the elderly, characterized by a heterogeneous clinical spectrum resulting from the pathological accumulation of alpha-synuclein in cortical and subcortical structures. The diagnosis of this condition represents a significant clinical challenge due to the overlap of manifestations with other dementias, especially Alzheimer’s disease and dementia associated with Parkinson’s disease. This chapter aims to synthesize the current scientific evidence regarding the diagnostic approach to LBD, with emphasis on clinical criteria, biomarkers, and emerging aspects that contribute to its early and accurate identification. LBD presents a distinct cognitive profile, with initial impairment of attentional, executive, and visuospatial functions, relative preservation of episodic memory in the initial phases, and the presence of cognitive fluctuations. Among the central clinical features, recurrent visual hallucinations, spontaneous parkinsonism, and REM sleep behavior disorder stand out, the latter being recognized as an important prodromal marker of synucleinopathies. The use of indicative biomarkers, such as dopaminergic functional neuroimaging exams, myocardial scintigraphy with ¹²³I-MIBG, polysomnography, and alpha-synuclein detection assays, has increased diagnostic accuracy. Furthermore, autonomic manifestations, alterations in central auditory processing, and emerging immunological mechanisms are being recognized as relevant components in understanding the pathophysiology of MCI (Mild Cognitive Impairment). The correct differentiation between MCI and Parkinson’s disease dementia, based on the one-year temporal rule, as well as the recognition of the frequent coexistence with Alzheimer’s disease pathology, are fundamental for adequate clinical management. Therefore, an integrated diagnostic approach, based on clinical criteria and biomarkers, is essential to reduce underdiagnosis and optimize care for patients with Lewy body dementia. DOI: https://doi.org/10.56238/sevened2026.002-004